Buckling behaviour of steel plate subjected to axial load / Mohd Fazarudin Abdullah@Zakaria - Abdullah@Zakaria, Mohd Fazarudin (1998)
This project is to study the buckling behaviour of steel plate subjected to axial load. Column specimens will be tested in Civil Engineering Laboratory and followed by the computer model in order to determine the stress distribution and the deflection. Modulus of elasticity, (E) will be taken from tensile test coupon. In the experiment and investigation reported here only one thickness i.e. 6 mm mild steel was chosen and rectangular sections, 50 mm x 6 mm and 300 mm height were tested. The rectangular columns were supported at both ends and subjected to a compressive load aligned with its centroidal axis. The failure load and deflection was recorded. The theoretical ultimate load was calculated using the effective width concept. This method was chosen because it gives a more true life picture of the actual behaviour of a compressed plate and plate type sections. For the case of steel plate sections the reduction in cross sectional area was taken into consideration. Experimental deflection will be used as a reference in order to iterate the modulus of elasticity, (E) in the calculation and computer analysis (ANSYS). Using the same value of axial load, (P) than compare the deflection between experimental and computer analysis. If the deflection is not equal than change the modulus of elasticity, (E) until get the same deflection.